Venous stenosis in chronic dialysis patients with a well-functioning arteriovenous fistula. (February 2016) - Shi, Yaxue; Zhu, Mingli; Cheng, Jiejun; Zhang, Jiwei; Ni, Zhaohui
Purpose: It is not clear whether patient who is dialyzing with a well-functioning vascular access may appear venous stenosis. The aim is to see the prevalence of central or other vein stenoses/occlusions in patients with asymptomatic, normal functioning fistulas. Methods: A total of 54 patients met the inclusion criteria. We performed angiography examinations for these patients and reviewed venography of the superficial and deep venous systems. Results: Among these patients, 21 (39%) were detected positive cases by the angiography, the remainder was negative cases. Thirteen of 54 (24%) had mild central venous stenosis (stenosis <50% diameter with or without collateral branch), 7/54 (13%) had upper arm vein system occlusion or stenosis, another one had anastomotic stenosis. There were no differences in fistula flow dynamics between those with venous abnormalities and those without such as blood flow rate, venous pressures, brachial arterial velocity, and brachial arterial flow rate. We also observed no significant differences in other variables between these two groups (including BMI, hemoglobin, albumin, gender, primary disease, URR, spKt/V P > 0.05). Conclusion: The frequency of venous lesion is not low in hemodialysis patients with a well-functioning AVF. To value the impact of these abnormalities on access, prognosis needs longer time follow-up.